Surgical aspects of cervical spinal cord injuries - Calvo Rubal, Antonio (Cirugía del Uruguay, 1982)
A surgical approach to rachimedullary cervical trauma is presented. This approach, takes into consíderation the constricting medullary effect and rachis stabi!ity as decisive parameters. The early fixation and reduction of the fracture luxation through surgery, facilita tes the recovery and the patient's neurological cares. The authors sponsor a posterior approach to the lesion of the irst vertebrae, and an anterior approach to the lesion of the other vertebrac. The use of a discectomy-raft bone-metallic plate to consolidate the reduction is preferred.